2011
DOI: 10.2320/matertrans.m-m2011803
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Flotation Process with De-Sliming and Attrition to Upgrade and Recover Cu and Mo from a Cu-Mo Flotation Tailing

Abstract: In some (Cu-Mo) mines around the world, Mo recovery is low due to poor liberation, fine dissemination in gangue minerals, and losses of Cu and Mo to tailing streams. Studies to recover these materials as a new resource will increasingly become an attractive option. In the current study, a flotation tailing sample obtained from a mine recovering only 40% Mo was re-floated to upgrade Cu and Mo. The sample containing 0.07% Cu and 0.01% Mo, was used in the study and the goal was to improve the grades to over 2.0% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…It has significantly contributed to the upgrade of mineral values thus confirming its attractiveness in flowsheet development where slimes impede value upgrades [55]. Elsewhere desliming has been reported to contribute to some value losses [56,57]. In the present study, significant gains in desliming prior to the flotation process were observed as shown in Figure 11.…”
Section: Relevance Of Deslimingsupporting
confidence: 77%
“…It has significantly contributed to the upgrade of mineral values thus confirming its attractiveness in flowsheet development where slimes impede value upgrades [55]. Elsewhere desliming has been reported to contribute to some value losses [56,57]. In the present study, significant gains in desliming prior to the flotation process were observed as shown in Figure 11.…”
Section: Relevance Of Deslimingsupporting
confidence: 77%
“…The grade of iron decreased with increasing the pH of slurry from pH 4 to pH 6 and increased further with increasing the pH of the slurry. The results obtained are verified that high pH value of the slurry has a positive effect on copper beneficiation due to the depression effect of pyrite (FeS 2 ) and gangue minerals including [21][22][23] . Result showed that collectorless flotation is possible to recover copper from the low-grade copper ore containing silicate.…”
Section: Effect Of Slurry Phsupporting
confidence: 54%
“…The benefits of desliming described in this report are supported by similar works done elsewhere. For instance, in the work conducted by authors [43], desliming was performed with the tailings from the first stage of the multi-stage flotation system using a 44 µm screen to remove the −44 µm slime fraction. The flotation was continued from second to fourth stage using the +44 µm fraction.…”
Section: Flotation Tests On Deslimed Materialsmentioning
confidence: 99%